Tumor necrosis factor-α-primed mesenchymal stem cell-derived exosomes promote M2 macrophage polarization via Galectin-1 and modify intrauterine adhesion on a novel murine model - Li, Jingman; Pan, Yuchen; Yang, Jingjing; Wang, Jiali; Jiang, Qi; Dou, Huan; Hou, Yayi (Frontiers in Immunology, 2022)
Intrauterine adhesion (IUA) is a condition caused due to damage or infection of the endometrium. It is characterized by continuous inflammation and following fibrosis and dysfunction. However, the current animal IUA models have several disadvantages, including complex operation, high mortality, and many extra distractions owing to opening of the abdominal cavity to expose the uterus. Mesenchymal stem cells (MSCs), which have been used in treatment of IUA, are heterogeneous and immunosuppressive. However, their therapeutic effect is not as good as expected. In this study, we successfully built a new murine IUA model, called electric tool-scratching IUA model, and applied it in our experiments to investigate the efficacy of tumor necrosis factor-α primed MSCs (T-MSCs). In the new model, we used a self-made electric tool that can cause mechanical damage to the endometrium without opening the abdominal cavity. Subsequently, we compared the therapeutic efficacy of untreated MSCs and TNF-α-pretreated MSCs on IUA. The results showed that TNF-α pretreatment could enhance the ability of MSCs to relieve inflammation and reduce endometrium fibrosis in IUA mice. Mechanistically, Galectin-1 in exosomes of TNF-α primed MSCs promoted endometrial macrophage polarization to M2 phenotype mainly through the Jak-STAT signaling pathway. Thus, our studies proposed an innovative mouse model and a better MSC treatment strategy for IUA.